The effects of topical steroid fears and concerns on patients with eczema: first TOPICOP© scale-based study in Saudi Arabia - Alharbi, Abdulmajeed A.; Alhetheli, Ghadah I.; Alqahtani, Reema; Alshehri, Mujahid (International Journal of Research in Dermatology, 2021)
Background: Topical corticosteroids (TCS) are the main treatment for eczema, which are often required for months (or years) to control the disease. Despite the well-known side effects of TCS, their efficacy and safety are well established when used appropriately. This study was conducted to assess the fears, concerns, and various practices of patients with eczema toward TCS in the Qassim region of Saudi Arabia. Methods: A cross-sectional survey-based study was conducted that targeted patients with eczema among all age groups and genders attending the dermatology outpatient clinics. There were no exclusions based on the type, severity, or duration of the disease. Results: A total of 105 patients with eczema were recruited for this study. It was revealed that 46.8% of participants stopped their treatment as soon as possible, which indicates immediate discontinuation of steroids after their eczema flares had subsided and improved. An interesting finding was that 38.3% of participants did not start their TCS treatment until the disease deteriorated rather than when flare-ups occurred. Conclusions: Exaggerated fears about TCS exist among patients with eczema and their care givers. This can result in non-adherence or wasting of many prescribed TCS preparations TCS. It is very important to understand and emphasize on the nature and extent of the prevalence of TCS fears to ensure that prompt, correct advice can be offered. Since dermatologists remain the most trusted source of information, there should be an emphasis on individual patient counseling and increased engagement in social media with pre-planned content.